ADAPTATION OF BIM WORKFLOW IN STRUCTURAL ENGINEERING PROJECTS & THE NEED TO ESTABLISH A NATIONAL BIM STANDARD - Thomas Thampy, Tony (2020)
The Introduction of the concept of BIM into the construction industry, have made significant changes to the working standards and workflow pattern. This thesis examines the said changes in comparison to the traditional working methods in all phases of project starting from pre-concept to demolition with respect to the structural engineering discipline. Case studies are done to check the typical workflow in a BIM environment for structural design. Thus analysing the skills required and deliverables that are to be produced in BIM working environment for optimum workflow. The BIM implementation strategies and the rate of BIM adaptation in 5 selected countries including UAE are analysed. The relation between national BIM standards and the rate of BIM implementation in the respective countries are also evaluated. The current BIM awareness in the UAE is also analysed by a market survey conducted among industry experts in the UAE, focusing on the obstacles for the implementation of a national BIM strategy. The adaptation of the BIM into the structural engineering workflow has shown many improvements in comparison to the traditional workflow such as software interoperability, ease of production of schedules and drawings, 3D representation of reinforcement and other technical data, etc. National mandates and standards in relation to BIM have shown to increase the rate of BIM adaption in respective countries and also achieve a sense of regularity in the construction industry and authority standards. From the market survey conducted, the professionals have expressed the need for similar BIM standardisation in the UAE and also the current obstacles for the same.